SOIL / WATER COUPLED ANALYSIS FOR CONSTRUCTION MANAGEMENT OF HIGHWAY EMBANKMENTS ON SOFT CLAY - T. Takeyama; T. Ishigaki; T. Mizuta; H. Ohta (International Association of Lowland Technology, 2009)
In the limited budget of highway construction, it is necessary to carry out the construction management which systematically utilizes management resources. This paper presents the applicability of soil / water coupled FE analysis for use in construction management of highway embankment on soft clay. At the first stage of analysis, the computer simulations of existing highway embankments on soft marine clay are conducted to verify their predictability. The constitutive model used in the analysis is an elasto-viscoplastic model proposed by Sekiguchi and Ohta (1977). At the second stage, the simulations of construction sequences, as case studies, with slow to fast banking rates are trialed to find better alternatives. It is a main point of the proposal to perform a construction management by fully utilizing the result of simulations for checking the stability of the foundation during construction.